In silico virtual screening of potent inhibitor to hamper the interaction between HIV-1 integrase and LEDGF/p75 interaction using E-pharmacophore modeling, molecular docking, and dynamics simulations. (August 2021) - Panwar, Umesh; Singh, Sanjeev Kumar
Graphical abstract: Highlights: Blocking the interaction between LEDGF/p75 and HIV-1 integrase is a pleasant therapeutic target. Potent ZINC natural compounds were virtually screened using e-pharmacophore modeling and docking approach. DFT & dynamics were analyzed on best hits and known compounds to confirm their energy states and stability with integrase. We conclude these compounds ZINC22077550 & ZINC32124441 could be novel therapeutics to fight against HIV-1 infection. Abstract: The rapid increase of HIV-1 infection throughout the globe has a high demand for a superior drug with lesser side effects. LEDGF/p75, the human Lens Epithelium-Derived Growth Factor is identified as a promising cellular cofactor with integrase in facilitating the viral replication in an early stage by acting as a tethering factor in the pre-integration to the chromatin. Therefore, the present study was designed to identify a potent inhibitor by applying an E-pharmacophore based virtual screening, molecular docking, and dynamics simulation approaches. Finally, ZINC22077550 and ZINC32124441 were best identified potent molecules with the efficient binding affinity, strong hydrogen bonding, and acceptable pharmacological properties to hamper the interaction between integrase and LEDGF/p75. Further, the DFT and MDS studies were also analyzed, and shown a favorable energetic state and dynamic stability then reference compound. In conclusion, we suggest that these findings could be novel therapeutics in the future and may increase the lifespan of individuals suffering from viral infection.